Minimal mosaicism, maximal phenotype: Discordance between clinical and molecular findings in two patients with tuberous sclerosis. Issue 3 (27th September 2018) - Byers, Heather M.; Jensen, Dana M.; Glass, Ian A.; Bennett, James T.
Abstract : Tuberous sclerosis complex (TSC) is an autosomal dominant neurocutaneous disorder characterized by hamartomatous growths in the brain, kidneys, lungs, skin, heart, and retina. TSC is caused by loss of function mutations in one of two tumor suppressor genes, TSC1 or TSC2 . Two‐thirds of individuals with TSC have de novo mutations, and individuals with postzygotic pathogenic variants in both TSC1 and TSC2 have been reported. The development of sensitive molecular methods, such as next generation sequencing, has led to an increased ability to detect low‐level mosaic variants, which are typically thought to have milder phenotypes because a smaller fraction of cells in the body harbor the mutation. Here, we describe two patients with TSC who had severe phenotypic involvement, but only low‐level mosaicism in TSC2 . Given this apparent discrepancy and concern about a missed constitutional variant, we sampled multiple tissues in both cases to confirm these mosaic mutations. Sampling of multiple tissues can be crucial in molecular diagnosis of mosaic TSC. These cases highlight, in general, challenges in molecular diagnosis of genetic conditions due to postzygotic mutations.